Looking for a miracle - Nickell, Joe (Prometheus Books, 1993)
An examination of miracle claims from the Shroud of Turin to levitation and inedia.
Keywords: Genezing; Paranormale verschijnselen; Relikwieën; Stigmata (theologie); Visioenen; Wonderen; Mental Healing; Miracles; Occultism; Parapsychology; Religion and Medicine; Religion and Science